2021
DOI: 10.1021/acs.inorgchem.0c02629
|View full text |Cite
|
Sign up to set email alerts
|

Nanocage-Based N-Rich Metal–Organic Framework for Luminescence Sensing toward Fe3+ and Cu2+ Ions

Abstract: Luminescent metal–organic frameworks (LMOFs) as sensors showing highly efficient detection toward toxic heavy-metal ions are in high demand for human health and environmental protection. A novel nanocage-based N-rich LMOF (LCU-103) has been constructed and characterized. It is a 2-fold interpenetrating structure built from N-rich {Zn6(dttz)4} nanocages extended by N-donor ligand Hdpa [H3dttz = 4,5-di­(1H-tetrazol-5-yl)-2H-1,2,3-triazole; Hdpa = 4,4′-dipyridylamine]. Notably, LCU-103 contains abundant N functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 63 publications
0
58
0
Order By: Relevance
“…Ln-MOFs materials have outstanding luminescence characteristics; that is, they have the advantages of large Stokes shift, high quantum yield and luminescence intensity, narrow emission spectrum range, flexible coordination mode, and long luminescence life. MOFs fluorescent probes are commonly used as sensors [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Hna et al [26] synthesised Ce-MOF to detect Fe 3+ , and Gai et al [27] synthesised dual-sensor Eu-MOF to detect Fe 3+ and Cr 2 O 7 2− .…”
Section: Introductionmentioning
confidence: 99%
“…Ln-MOFs materials have outstanding luminescence characteristics; that is, they have the advantages of large Stokes shift, high quantum yield and luminescence intensity, narrow emission spectrum range, flexible coordination mode, and long luminescence life. MOFs fluorescent probes are commonly used as sensors [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Hna et al [26] synthesised Ce-MOF to detect Fe 3+ , and Gai et al [27] synthesised dual-sensor Eu-MOF to detect Fe 3+ and Cr 2 O 7 2− .…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the structural tunability and tailorability, metal-organic complexes have witnessed astonishing achievement in the last two decades. [58][59][60][61][62][63][64][65] The sound assembly of metal ions and predesigned ligands provides a wide platform to generate various functionalized hybrid materials under the guidance of crystal engineering. In this work, we utilise the ET and crystal engineering strategies to predesign CHPMs with potential multiple photoresponsive properties via the synergy of paramagnetic metal ion (Dy 3 + ), ED-ligand (benzene-1,2,3tricarboxylic acid, H 3 BTA) and EA-ligand (1,10-phenanthroline, phen) (Figure 1).…”
mentioning
confidence: 99%
“…DFT studies revealed the HOMO-LUMO energy difference of unbound probe as 1.07 eV and [probe-Zn 2+ ] has a decrement to 0.15 eV, confirming the strong complexation. The luminescent metal organic frameworks (LMOFs) as nanocages to recognize Fe 3+ and Cu 2+ ions in trace quantity was designed and synthesized by Li et al [53] The fluorescent quenching activity of the nanocages was due to their weak interaction with the metal ions at N-rich sites. DFT calculations confirmed the uncoordinated N atoms in the nanocage interact weakly with the metal ions and hence the fluorescence was quenched.…”
Section: Heavy Metal Sensormentioning
confidence: 99%